Intertextuality in Translating Yan Lianke's Novel "Hard as Water" - Cuadra-Mora, Belén (Íkala, Revista de Lenguaje y Cultura, 2024)
Intertextuality plays a prominent role in any text’s universe of discourse. This feature, present in all cultures, holds a special relevance in the Chinese literary tradition, and thus poses singular challenges for translators working from a textual tradition as distant, in principle, as Spanish. This paper analyses the relationship between intertextuality and translation based on the impact of model operas in the novel Hard like water by the Chinese writer Yan Lianke. To do this, it initially contextualises the novel following an intertextuality approach, vis-ible both in the plot and in the style of the work, and then dissects and provides examples of the strategies employed in its translation, which show a combination of conservative and innovative elements. In this way, the paper provides empiri-cal evidence of the relationship between intertextuality and literary translation in the Chinese-Spanish combination, by proposing a framework of analysis that abounds in a conception of translation as a space of confluence and divergence of textual traditions.